Case histories of slope protection by HDPE Geocells - Neoh, C.A; Har, L.Y.K; Siti Farhanah, SM Johan; Tan, Poi Cheong (Penerbit UTHM, 2024)
It has been widely reported that infiltration accounts for 90 % of slope failures (NAHRIM, 2021). Proper and effective slope protection can reduce infiltration significantly. In fact, bare or poorly protected slopes have 3 to 5 times higher rate of infiltration when compared with well protected slopes. Cut slopes with difficult and adverse conditions such as high cut slopes with acidic graphitic phyllite or schist or highly erodible sandy silt or rocky slope, etc., cannot be effectively protected by normal slope protection methods such as hydroseeding or turfing. Though guniting or sprayed concrete can be effectively used to protect such difficult cut slope conditions, the ungreen or unaesthetic or unenvironment-friendly appearance is generally and increasingly not acceptable by general public and government authorities including JKR Malaysia. Recently, geosynthetic product with generic name called HDPE (high density polyethylene) geocells have been proposed and accepted to be used to vegetate difficult steep acidic and rocky slopes successfully in respect to reduce infiltration to practically nil and to provide green pleasing slope finishes. Unlike normal polymers, HDPE is a durable polymer, inert to chemical attacks and its strength is practically unaffected by UV rays or acids. It is found that HDPE geocell confinement system .